Comparison between Sublay & Onlay Mesh hernioplasty in Ventral Wall Abdominal Hernia Repair - Muhammad Umair Samee, Muhammad Furqan Sharif, Hafiz Muhammad Abdullah Tahir, Mirza Zeeshan Sikandar, Fahad Ahmad Khan, Hassan Ashfaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Aim: Onlay and sublay repairs are the two surgical methods most commonly employed in ventral hernia patients. The repair of a ventral hernia is one of the most common surgical procedures performed globally. The results of simple ventral hernia onlay and sublay mesh repair methods were compared in this study to compare the results of onlay and sublay mesh ventral incisional hernia repair procedures. To investigate the frequency of seroma, wound infection, and wound disruption in patients with ventral abdominal hernias who had onlay and sublay mesh plasty. Incisional hernia (IH) is a very common surgical complication. Study design: Prospective Randomized Control Trial Place and duration of study: This study was done in department of General surgery at Central Park teaching Hospital, Lahore during a period of 4 months that span from October 2021 till January 2022. Methodology: This prospective research included 100 adults with primary or secondary uncomplicated ventral hernias. The onlay mesh repair procedure was used in both groups B (n = 50) and A (n = 50). We randomly assigned participants to one of two therapy groups using a computer-generated randomization process. The procedure’s length, the length of the drain, the duration of any wound infections, the length of the post-op hospital stay, and any short-term recurrence were all noted. Results: When compared to the sublay group, the onlay group had a substantially shorter median operational time (52 vs. 91 min., respectively). However, in terms of wound complications and postoperative pain, the sublay group beat the control group significantly. Disease recurrence occurred in 8% and 3% of patients in groups A and B, respectively. Practical Implication: Sublay mesh repair, which is an alternative to onlay mesh repair, can be used to treat all types of ventral hernias. Conclusion: Sublay mesh repair, which is an alternative to onlay mesh repair, can be used to treat all types of ventral hernias. Mesh-related issues are associated with long drainage times, seroma development, wound infection, and recurrence. In terms of postoperative discomfort and wound complications, sublay mesh repair is preferred than onlay mesh repair for treating incisional hernias. The recurrence rates of the two procedures are comparable. Keywords: Ventral Hernia, Onlay Mesh Repair, Sublay Mesh Repair